Implications of Curug Cileat's Tourist Attraction Factors According to Prospective Tourists' Perceptions of Economic Sustainability - Jojo Jojo; Eksa Audya Gunawan; Panji Agnyoto; Ana Frasipa; Asep Kurniawan; Mutqi Sopiawadi; Devy Widya Apriandi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This study aims to analyze the implications of tourist attraction factors at Curug Cileat based on prospective tourists' perceptions toward local economic sustainability in Cisalak District, Subang Regency. The observed attraction factors include natural beauty, accessibility, facilities, price, and promotion. The research employs a quantitative approach using questionnaires distributed to 50 respondents. The findings reveal that tourist attraction factors significantly positively influence prospective tourists' perceptions, which in turn positively impact the local community's economic sustainability. Natural beauty and accessibility are the dominant elements affecting perception and revisit intention. These results emphasize that sustainable management of tourist attractions not only enhances tourist satisfaction and perception but also strengthens the local economy. Practical implications highlight the importance of environmental conservation, improved accessibility, facility enhancement, and digital-based promotion to support sustainable tourism development at Curug Cileat.